Effects of Ultrasonic-Microwave-Assisted Technology on Hordein Extraction from Barley and Optimization of Process Parameters Using Response Surface Methodology - Xiao Guan; Lv Li; Jing Liu; Sen Li (Journal of Food Quality)
We investigated the process intensification of ultrasonic-microwave-assisted technology for hordein extraction from barley. Response surface methodology was utilized to optimize the extraction conditions and to analyze the interaction between four selected variables: temperature, microwave power, ultrasonic power, and extraction time. The validated extraction yield of hordein reached 8.84% at 78°C, microwave power 298 W, and ultrasonic power 690 W after 20 min as optimum conditions. Compared with traditional water-bath extraction (4.7%), the ultrasonic-microwave-assisted technology effectively increased the hordein extraction yield and shortened the extraction time. According to the obtained quadratic model (R2 = 0.9457), ultrasonic power and extraction time were the first two significant factors. However, temperature limited the effects of other factors during extraction. SDS-PAGE and scanning electron microscopy were used to identify the hordein extract and to clarify the difference between the two hordein fractions extracted with new and traditional methods, respectively. Ultrasonic-microwave-assisted technology provided a new way to improve hordein extraction yield from barley and could be a good candidate for industrial application of process intensification.